Postmortem Skeletal Microbial Community Composition and Function in Buried Human Remains - Alexandra L. Emmons; Amy Z. Mundorff; Katharina M. Hoeland; Jonathan Davoren; Sarah W. Keenan; David O. Carter; Shawn R. Campagna; Jennifer M. DeBruyn (mSystems, 2022)
ABSTRACT Bones and teeth can provide a lasting resource to identify human remains following decomposition. Bone can support dynamic communities of micro- and macroscopic scavengers and incidental taxa, which influence the preservation of bone over time. Previously we identified key microbial taxa associated with survivability of DNA in bones of surface-decomposed human remains, observing high intra- and interindividual variation. Here we characterized the postmortem bone microbiome of skeletal remains in a multi-individual burial to better understand subsurface bone colonization and preservation. To understand microbial community origins and assembly, 16S rRNA amplicon sequences from 256 bone and 27 soil samples were compared to bone from individuals who decomposed on the ground surface, and human gut sequences from the American Gut Project. Untargeted metabolomics was applied to a subset of 41 bone samples from buried remains to examine potential microbe–metabolite interactions and infer differences related to community functionality. Results show that postmortem bone microbial communities are distinct from those of the oxic surface soils and the human gut. Microbial communities from surface-deposited bone and shallow buried bone were more similar to those from soils, while bones recovered from saturated areas deeper in the grave showed increased similarity with human gut samples with higher representation of anaerobic taxa, suggesting that the depositional environment affected the established bone microbiome. Correlations between metabolites and microbes indicate that phosphate solubilization is likely an important mechanism of microbially mediated skeletal degradation. This research expands our knowledge of microbial bone colonizers, including colonizers important in a burial environment. IMPORTANCE Understanding the microbes that colonize and degrade bone has important implications for preservation of skeletal elements and identification of unknown human remains. Current research on the postmortem bone microbiome is limited and largely focuses on archaeological or marine contexts. Our research expands our understanding of bone microbiomes in buried remains by characterizing the taxonomic and metabolic diversity of microbes that are colonizing bone after a 4-year postmortem burial interval and examines the potential impact of microbial colonization on human skeletal DNA preservation. Our results indicate that the postmortem bone microbiome is distinct from the human gut and soil. Evidence from combined metabolomic and amplicon sequencing analysis suggests that Pseudomonas and phosphate solubilization likely play a role in skeletal degradation. This work provides important insight into the types and activities of microbes controlling the preservation of buried skeletal remains.